Steven Friedman (in collaboration with Judith Hudson), Race, Class and Power: Harold Wolpe and the Radical Critique of Apartheid : A particularly timely contribution to South Africa’s intellectual history (Historia, 2021)
This intellectual biography of one of South Africa's leading white, anti-apartheid academic radicals, arrives during a feverish phase of the country's post-apartheid life. A new generation of black student radicals are staking a claim to the "radical" mantle in protests currently rocking the country's university campuses. If the work by the subject of Steven Friedman's book, Harold Wolpe and other Marxist theorists were de rigeur for white student radicals in the 1970s, Franz Fanon and Steve Biko and talk of "decolonisation" roll off the lips of post-apartheid student activists. What then does Friedman's biography have to offer in the contemporary moment where the now somewhat older white academic left is derided as "irrelevant" and as presenting obstacles to radical change?